The Development of Human Genetics at the National Research Centre, Cairo, Egypt: A Story of 50 Years - Temtamy, Samia A (Annual review of genomics and human genetics, 2019)
This article describes my experiences over more than 50 years in initiating and maintaining research on human genetics and genomics at the National Research Centre in Cairo, Egypt, from its beginnings in a small unit of human genetics to the creation of the Center of Excellence for Human Genetics. This was also the subject of a lecture I gave at the 10th Conference of the African Society of Human Genetics, held in Cairo in November 2017, after which Professor Michèle Ramsay, president of the society, suggested that I write an autobiographical article for the . I hope that I succeeded in the difficult assignment of summarizing the efforts of a researcher from a developing country to initiate and maintain the rapidly advancing science of human genetics and genomics in my own country and make contributions to the worldwide scientific community.